Beruflich Qualifizierte im Studium Analysen und Konzepte zum Dritten Bildungsweg - Elsholz, Uwe (W. Bertelsmann Verlag, 2015)
The separation of academic and vocational training has a long tradition in Germany. The introduction of third level study courses without A level prerequisite was supposed to make the education system less exclusive. Against a background of increasing academic focus in the business world, however, interest in "studies on the basis of existing professional qualifications" is on the rise. The articles contained in the volume offer information about current studies, present the current status quo of research and follow up on biographies of students who chose "third chance education". The volume deals with challenges in education policy, with didactic-curricular and theoretical aspects, as well as with to date unanswered questions regarding research and development. Interest is not only focused on third level education - the entire traditional German education system is currently undergoing change.